Participação do árbitro de vídeo (VAR) na copa do mundo da fifa de 2018 - Fernandes Júnior, Rodrigo [UNESP] (2018)
The video referee (VAR) began to be used to meet the demands of football and its lovers. The objective of the present study was to quantify the interventions of the VAR during the 2018 FIFA World Cup, classify the interventions in the 4 moments that can occur (goal, penalty, red card and player identification) and quantify the decision change of the arbitrator, depending on the assistance of the VAR. The sample consisted of the 64 games of the competition, counting the 90 minutes of game and additions and also the minutes of the extra times (extension) when necessary. The data were collected from interviews of FIFA representatives and surveys made by professionals of the Brazilian sports communication. According to FIFA, the results of the use of the VAR obtained in the 64 games were: 455 incident checks (average of 7.1 per game) and 20 revision of bids that occurred intervention in the game. According to the Folha de São Paulo, of the 23 interventions of the VAR in the game: 16 were in penalty throws (for marking and to undo a possible mistaken marking); 4 were goals scored (for possible lack or impediment); 2 moments were related to the possible application of the red card (which were warned with yellow card by decision of the main referee); and only 1 moment when the player identification was required (the referee had applied the yellow card to a player who had not committed the infraction). In addition, of the 23 reviews, in 16 of them needed the use of the field television and only in 7 was done through the electronic point (radio). In total, 15 times the main referee changed his decision when reviewing the bid and only in 8 moments, even reviewing the bid, he maintained his initial decision. According to representatives of FIFA, this was the best World Cup in history... (Complete abstract electronic acess below)